2012
DOI: 10.1161/circulationaha.111.063198
|View full text |Cite
|
Sign up to set email alerts
|

Collagenase Total Occlusion-1 (CTO-1) Trial

Abstract: Background— Percutaneous interventions for chronic total occlusions have low success rates, primarily because of failure of guide wire crossing. Collagen-rich matrix constitutes the main barrier to chronic total occlusion crossing. In preclinical studies, local delivery of a bacterial collagenase formulation improved guide wire crossing. The Collagenase Total Occlusion-1 (CTO-1) Trial is a phase I, dose-escalation trial to assess the safety and efficacy of collagenase therapy to facilitate guide wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Also, collagenase was loaded on GO and GO-CS to probe its activity before/after loading using gel zymography analysis. Collagenase (matrix metalloproteinase, MMP) is one of the important therapeutic proteins in medical treatments for several diseases, including necrotic tissue, Dupuytren’s contracture and Peyronie 45 , chronic total occlusion 46 , lumbar disc herniation 47 , oral submucus fibrosis 48 , and tumors 49 50 .…”
mentioning
confidence: 99%
“…Also, collagenase was loaded on GO and GO-CS to probe its activity before/after loading using gel zymography analysis. Collagenase (matrix metalloproteinase, MMP) is one of the important therapeutic proteins in medical treatments for several diseases, including necrotic tissue, Dupuytren’s contracture and Peyronie 45 , chronic total occlusion 46 , lumbar disc herniation 47 , oral submucus fibrosis 48 , and tumors 49 50 .…”
mentioning
confidence: 99%
“…The expectation is that collagenase would degrade connective tissue for rapid and reliable wire navigation. A dose finding study reported excellent clinical results 24 . In TOSCA-5 trial, 75 CTO patients with prior documented failed PCI were randomized to placebo control or either 900 ug or 1200 ug intra-microcatheter injection of the collagenase the day before they underwent antegrade CTO PCI.…”
Section: Pathophysiology Of Bodymentioning
confidence: 99%
“…20 A novel approach under investigation involves using local injections of collagenase to enzymatically degrade collagenous CTOs. A first-in-man phase 1 clinical trial using collagenase in coronary CTOs 39 showed improvement in facilitating guidewire passage. Ultrasound stimulated microbubbles have also been investigated to potentiate the effects of collagenase penetration into the lesion.…”
Section: Chronic Total Occlusionsmentioning
confidence: 99%